2013
DOI: 10.1002/anie.201303783
|View full text |Cite
|
Sign up to set email alerts
|

The X‐ray Crystal Structure of a Cuprate–Carbonyl π‐Complex

Abstract: Why is it π? The first X‐ray crystal structure of a cuprate–carbonyl π‐complex has been obtained for the intermediate prepared from Me2CuLi and fluorenone (see scheme). It is also the first structure of a π‐complex between an organocuprate and a double bond of any kind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The product was extracted with THF,a nd the organic phases were dried in vacuum to give product 3 as ag reen solid (103 mg, 0.152 mmol, 83 %). ( Ph dpbp)FeCl (5):N aphthalene (141.2 mg, 1.1 mmol) was dissolved in THF (20 mL) in the glovebox at RT.Alump of Na 0 was added and the mixture was stirred for 3h to give ad ark green solution. FeCl 2 (115.3 mg, 0.909 mmol) was suspended in THF (8 mL) in a vial, and Ph dpbp (500.2 mg, 0.908 mmol) was dissolved in another vial in THF (12 mL).…”
Section: General Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The product was extracted with THF,a nd the organic phases were dried in vacuum to give product 3 as ag reen solid (103 mg, 0.152 mmol, 83 %). ( Ph dpbp)FeCl (5):N aphthalene (141.2 mg, 1.1 mmol) was dissolved in THF (20 mL) in the glovebox at RT.Alump of Na 0 was added and the mixture was stirred for 3h to give ad ark green solution. FeCl 2 (115.3 mg, 0.909 mmol) was suspended in THF (8 mL) in a vial, and Ph dpbp (500.2 mg, 0.908 mmol) was dissolved in another vial in THF (12 mL).…”
Section: General Considerationsmentioning
confidence: 99%
“…The p complexes of carbon-carbon and carbon-heteroatom multiple bonds are reactive intermediates in al argen umber of catalytic reactions, which includesh ydrogenations, hydrofunctionalizations, oligo-and polymerizations. The latter,l ess common binding mode has been proposed in intermediate structures for the Cu-catalyzed addition of Grignardr eagents, [5,6] Ru-catalyzed hydrogenation reactions, [7,8] and oxidative additiono fa rylketone CÀCb onds. [4] The polarity of the carbon-oxygen double bonds in aldehydes and ketones sets them apart amongst p-binding ligands.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8a] Lewis acids are expected to prevent the coordination of the magnesium to the carbonyl moiety, thereby allowing the catalytic pathway to outcompete reduction. [11] A survey of Lewis acids (entries [9][10][11][12][13], demonstrated that in the presence of CeCl 3 , both the selectivity and the enantioselectivity improved (compare entries 1 and 9). The best selectivity (2 a/3 a = 3:1) was obtained when BF 3 ·Et 2 O was used as an additive, but at the cost of a drop in e.r.…”
mentioning
confidence: 99%